Monitoring of green areas in the University of Guadalajara through image processing in an HPC environment - Martín Pizano-Moreno; Jaime Ibarra-Nuño; Verónica Lizette Robles-Dueñas (Revista Colombiana de Computación)
Evaluation and monitoring of vegetation in urban areas is used for the management of natural resources and urban planning. This information has become more important than ever due to climate change. This work proposes the use of drones or Unmanned Aerial Vehicle (UAV) to make these vegetation inventory and process the acquired images using the photogrammetry software OpenDroneMap (ODM) in a high performance computer under Singularity and Snakemake. These tools can generate a big image map of the interested zone which can be used to study the future condition and health of vegetation.